P-108 Clinical Aspects and Prognoses of Patients with Inflammatory Bowel Disease and Autoimmune Liver Disease. (February 2017) - Vilela, Eduardo; Rocha, Henrique
Abstract : Background: Inflammatory bowel diseases (IBD) are associated with auto-immune liver diseases (AILD) and numerous studies have been published, however, almost all of them have focused on Primary Sclerosing Cholangitis (PSC). Methods: This is a retrospective, observational, case-control study that aimed at evaluating the clinical features of PSC and non-PSC auto-immune diseases in patients with IBD and comparing the course of both groups. Distribution of data was assessed by normality test (Shapiro-Wilk). Chi-square test was used to assess association between variables and any variables with P < 0.2 were included in regression binary logistic model. P values <0.05 were considered statistically significant. Results: Twenty-four patients were included. The mean age was 40.5 years (±14.3) and 14 were males (58.3%). Ulcerative colitis was present in 20 patients (83.3%) and Crohn's disease in 4 (16.7%). The median follow-up time frame was 7.5 years (1–28 yr). PSC was present in 16 patients (66.7%) and non-PSC in 8 (33.3%). Variant type of auto-immune hepatitis with cholestasis was present in 3, auto-immune hepatitis and PSC small duct overlapping syndrome in 2, autoimmune cholangiopathy in 2 and primary biliary cholangitis in 1. The median IBD diagnosis time frame was 6.5 years (0–28 yr). The median of liver disease diagnosis time was 4.5 years (1–26). Twenty patients underwent liver biopsy and of these, 12 (60%) were staged as F0 or F1 Metavir Classification and 8 (40%) were F2 or F4. Portal hypertension was observed in 4 patients at time of diagnosis and 2 of them underwent liver transplant. Colon adenocarcinoma was detect in 1 patient and there were 2 deaths. There was no differences between 2 groups in regards to diagnosis time frame, drug therapy, liver disease staging, liver transplantation, need for proctocolectomy and death. When multiple logistic regression was performed to evaluate factors associated with liver transplantation it was observed that only liver disease diagnosis time frame persisted with P <0.05 ( P = 0.016). The value of Odds Ratio was 1.34 (95% CI, 1.057–1.705). Conclusions: Clinical features and evolution of both groups were the same. However, this population had an increased chance of liver transplantation of 34% for each year of diagnosis. So, in 10 years, the chance of transplantation is 34 times higher.